Does Ozone-Water Complex Produce Additional OH Radicals in the Atmosphere? - Jin, Bing; Su, Man-Nung; Lin, Jim Jr-Min (My University, 2012)
Ozone-water complex has been thought to play a role in producing atmospheric OH radicals through its photolysis. Here, we re-examined the absorption cross-section of the ozone-water complex with a new method to tell whether the above speculation is valid. With argon solvation and photoionization by tunable vacuum ultraviolet light, we were able to selectively probe the ozone-water 1:1 complex. The measured cross-section of the complex is only similar to the sum of the cross-sections of ozone and water monomers at 157.6, 248.4, and 308.4 nm. In addition, we did not observe any absorption of the complex at 351.8 nm. The results indicate that the OH production through the photolysis of the ozone-water complex is much slower than previously thought.